Demographic performance of local sheep and goat breeds in two agro-ecological zones in Egypt - Abdel-Sabour T.; Valls-Fox H.; Messad S.; Mansour H.; Osman M.; El-Sayed M.; Aboul Naga A.; Alary V. (Efficiency and resilience of forage resources and small ruminant production to cope with global challenges in Mediterranean areas, 2021)
Small breeders in Egypt raise locally adapted sheep and goats breeds, which have the ability to produce and reproduce under the prevailing harsh conditions. Improving resilience of their production system is a major challenge to support socioeconomic development. However, little is known about the productive abilities of these breeds in small farming systems. The present work is an attempt to assess the performance of local breeds in small farming systems, and their capacity to cope with feed scarcity and harsh climatic conditions. In 2018, a retrospective survey was conducted over 12 month period to assess demographic rates of 25 local Barki sheep and goat flocks in the rain-fed area of Coastal Zone of Western Desert (CZWD) and 28 local Saidi sheep and goat flocks under the hot intensive agriculture system in Upper Egypt (UE). Flocks are larger, reproductive performance and offtake rates are higher (and mortality lower) in the CZWD, a region specialized in small ruminant breeding whereas it remains a secondary activity in Upper Egypt. The marketing season is mainly during Korban Eid festival. Their main challenges are frequent incidence of drought in the CZWD and high prices of feed stuffs in both sites. Our study suggests breeders have different strategies in UE and the CZWD when confronted with feed shortage. Breeders in the CZWD purchase feed to maintain high herd productivity whereas in UE small ruminant breeding is a minor activity with less productive animals that are resilient to feed shortage.
1. Joint meeting of the FAO-CIHEAM Networks on Sheep and Goats (Subnetworks on Nutrition and Production Systems) and on Mediterranean Pastures, 2019/10/23-25, Meknes (Morocco)